IMPLEMENTASI METODE QUALITY FUNCTION DEPLOYMENT DAN METODE SERVQUAL DIMENSI KEPARIWISATAAN GUNA PERBAIKAN KUALITAS PARIWISATA PANTAI KEBUMEN (Studi Kasus pada Pantai Logending, Pantai Manganti, Pantai Suwuk, Pantai Petahanan, dan Pantai Brencong) - Trifiyanto, Kabul; Susilowati, Ika (JURNAL AKUNTANSI DAN MANAJEMEN, 2018)
Kebumen tourism is dominated by south coast destination objects with combat routes ranging from half to two hours drive from the city center. Since 2015 tourist visits have increased, but on average only 14%. This is not comparable with the budget issued by the government to date which focuses on tourism infrastructure and the opening of new objects, especially coastal areas. According to preliminary studies the cause is because of visitor dissatisfaction with the quality of services provided, especially coastal tourism. So as to provide recommendations for improvements in tourism services in this study, the quality function deployment (QFD) method is based on servqual evaluation specifically for tourism dimensions. There are 43 variables used to define the quality of service dimensions of tourism for visitors. By using additional kano models, 12 critical variables were obtained. Then the critical variable produces 16 technical responses through the house of quality method for later as a recommendation for improvement. With the priority of repairs are; making tourist management SOPs, adding cleaners, and adding a viewing post/spot